2009
DOI: 10.1128/aem.02629-08
|View full text |Cite
|
Sign up to set email alerts
|

Free-Living Protozoa in Two Unchlorinated Drinking Water Supplies, Identified by Phylogenic Analysis of 18S rRNA Gene Sequences

Abstract: Free-living protozoan communities in water supplies may include hosts for Legionella pneumophila and other undesired bacteria, as well as pathogens. This study aimed at identifying free-living protozoa in two unchlorinated groundwater supplies, using cultivation-independent molecular approaches. For this purpose, samples (<20°C) of treated water, distributed water, and distribution system biofilms were collected from supply A, with a low concentration of natural organic matter (NOM) (<0.5 ppm of C), and from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 71 publications
5
70
0
3
Order By: Relevance
“…Modeling of data from a biofilm-batch model indicated that amoebae can only multiply when a threshold concentration of prey bacteria is reached (Kuiper, 2006). Valster et al (2009Valster et al ( , 2011) indicated that the growth of H. vermiformis in drinking water distribution systems is limited at low biofilm concentrations or at ATP concentrations of ≤1 ng L −1 . A number of eukaryotic sequences from the WSW biofilm were related to those of species unlikely to live in biofilm systems, such as Arthropoda and Chordata in Metazoa, and Spermatophyta in Viridiplantae.…”
Section: Eukaryotic Communitiesmentioning
confidence: 99%
“…Modeling of data from a biofilm-batch model indicated that amoebae can only multiply when a threshold concentration of prey bacteria is reached (Kuiper, 2006). Valster et al (2009Valster et al ( , 2011) indicated that the growth of H. vermiformis in drinking water distribution systems is limited at low biofilm concentrations or at ATP concentrations of ≤1 ng L −1 . A number of eukaryotic sequences from the WSW biofilm were related to those of species unlikely to live in biofilm systems, such as Arthropoda and Chordata in Metazoa, and Spermatophyta in Viridiplantae.…”
Section: Eukaryotic Communitiesmentioning
confidence: 99%
“…Most information on community composition and abundance of FLP in freshwater environments has been obtained by using cultivation methods and microscopy. Recently, however, the presence and identities of such organisms in drinking water supplies in temperate regions have been studied by using molecular methods for detection and identification (33,51). In two groundwater supplies in the Netherlands a total of 127 operational taxonomic units (OTUs) of FLP were identified based on their 18S rRNA gene sequences.…”
mentioning
confidence: 99%
“…detekovali Hartmannellu vermiformis v distribučnom systéme vody, kde bola asociovaná so zvý-šenou koncentráciou organickej hmoty (7,9 ppm uhlí-ku) a aktívnej biomasy meranej ako ATP (10,6 g.l -1 ) (20). Loret a kol.…”
Section: (2)unclassified
“…Valster a kol. (20) ukázali, že vyššia koncentrácia Hartmannella vermiformis bola získaná v letnom období, ako na jeseň, na tom istom odberovom mieste.…”
Section: Výskyt Améb V Distribučnom Systéme Pitnej Vodyunclassified
See 1 more Smart Citation